Pengaruh Return On Asset (ROA), Return On Equity (ROE), dan Earning Per Share (EPS) terhadap Harga Saham - Rika Mulita; Elma Muncar Aditya (Jurnal Ilmiah Aset, 2012)
This research aimed to find out the influence of Return On Asset (ROA), Return On Equity (ROE) and Earning Per Share (EPS) on the stock price of Wholesale and Retail Trade companies listed in Indonesia Stock Exchange. The sampling technique used was purposive sampling. There were 22 companies that could be analysed. The strategy analysis used in this research was multiple linier regression. From the analysis results it showed that ROA did not influence the stock price. While ROE and EPS significantly influenced the stock price.